2016
DOI: 10.1002/jcp.25300
|View full text |Cite
|
Sign up to set email alerts
|

Light/Dark Environmental Cycle Imposes a Daily Profile in the Expression of microRNAs in Rat CD133+ Cells

Abstract: The phenotype of primary cells in culture varies according to the donor environmental condition. We recently showed that the time of the day imposes a molecular program linked to the inflammatory response that is heritable in culture. Here we investigated whether microRNAs (miRNAs) would show differential expression according to the time when cells were obtained, namely daytime or nighttime. Cells obtained from explants of cremaster muscle and cultivated until confluence (∼20 days) presented high CD133 express… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 69 publications
0
7
0
Order By: Relevance
“…Similarly, maternal melatonin regulates fetal organogenesis and functions, such as adrenal gland, that are critical for the successful adaptation of the neonate to extra-uterine environment [83]. Furthermore, some studies show that both light/dark environmental cues [84] or melatonin treatment [85] turns on/off microRNA programs that control the REDOX state of cells after many complete proliferative cycles, favoring a longlasting cardioprotective state. In addition, melatonin treatment affects oocytes DNA methylation pattern, reversing the effects of oocyte aging [86].…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, maternal melatonin regulates fetal organogenesis and functions, such as adrenal gland, that are critical for the successful adaptation of the neonate to extra-uterine environment [83]. Furthermore, some studies show that both light/dark environmental cues [84] or melatonin treatment [85] turns on/off microRNA programs that control the REDOX state of cells after many complete proliferative cycles, favoring a longlasting cardioprotective state. In addition, melatonin treatment affects oocytes DNA methylation pattern, reversing the effects of oocyte aging [86].…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, the effects of melatonin on memory and neural loss (Wang et al, 2013) and on breast tumour response (Lee et al, 2013) are mediated by the differential expression of miRNAs. In physiological conditions, next-generation deep sequencing has indicated two distinct miRNA expression profiles in day-and night-time endothelial cells (Marçola et al, 2016). Night-time cells show a more complex biological network that is strongly controlled by five miRNAs, whilst only two miRNAs are overexpressed in daytime cells.…”
Section: Circulating Melatoninmentioning
confidence: 99%
“…Interestingly, miRNAs can also regulate the expression of MT 1 receptors (Zhu et al, 2014). It has recently been reported that the expression of miRNAs can vary in a daily pattern (Marcola et al, 2016), which introduces an additional bias regarding the time when data are collected. Because miRNAs are highly contextdependent, it is likely that they greatly contribute to the system bias on melatonin receptors signalling.…”
Section: Micrornasmentioning
confidence: 99%